Hormonal and non-hormonal control of glycogen synthesis — Control of transferase phosphatase and transferase I kinase - Larner, J.; Villar-Palasi, C.; Goldberg, N.D.; Bishop, J.S.; Huijing, F.; Wenger, J.-I.; Sasko, H.; Brown, N.B. (Advances in enzyme regulation, 1968)
Transferase, the enzyme that catalyzes the synthesis of the α-1,4 linkages of glycogen, is subject to control by several mechanisms including hormonal as well as non-hormonal. These controls are observed to occur rapidly in a number of tissues which are sensitive to the actions of the hormones. An important biochemical mechanism consists of interconverting two forms of the enzyme with second stage interconverting enzymes. These catalyze the phosphorylation and dephosphorylation of the two forms of transferase. The site of the non-hormonal control by glycogen is identified as the phosphatase, while the site of the hormonal control by insulin and epinephrine, the kinase. Insulin acts at the kinase site to bring about a greater dependence on cyclic AMP and thus inactivate the kinase, with no decrease in cyclic adenylate tissue concentrations. Epinephrine acts to increase tissue levels of cyclic adenylate, and thus promote kinase action.